2021
DOI: 10.3390/cryst11020122
|View full text |Cite
|
Sign up to set email alerts
|

Studying the C–H Crystals and Mechanical Properties of Sustainable Concrete Containing Recycled Coarse Aggregate with Used Nano-Silica

Abstract: The present study aims to replace 30%, 40%, and 50% of the natural coarse aggregate (NCA) of concrete with recycled coarse aggregate containing used nano-silica (RCA-UNS) to produce a new sustainable concrete. Three groups of concrete are made and their mechanical properties and microstructure are studied. In the first group, which was the control group, normal concrete was used. In the second group, 30%, 40%, and 50% of the NCA were replaced with coarse aggregate obtained from crushed concrete of the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 42 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…In the construction industry, the demand for lime and cement has increased, increasing their cost. Therefore, long-time efforts have been carried out to use waste from the manufacturing process as admixture [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the construction industry, the demand for lime and cement has increased, increasing their cost. Therefore, long-time efforts have been carried out to use waste from the manufacturing process as admixture [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CR-modified bituminous binders had stronger viscosity and temperature resistance than the conventional bituminous binders [ 29 ]. In considering the rheological properties, penetration, softening point and specific gravity, the CR modifier gives better mechanical properties as compared to conventional asphalt concrete [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nano TiO 2 can also extend the time it takes for cement to hydrate. Shahbazpanahi et al [31] reported that, with 0.5% content added to cement, a combination of 30% natural and 70% recycled coarse aggregates can produce sustainable concrete.…”
Section: Introductionmentioning
confidence: 99%